2018
DOI: 10.1017/s1368980018002161
|View full text |Cite
|
Sign up to set email alerts
|

Trends in sweetened beverages consumption among adults in the Brazilian capitals, 2007–2016

Abstract: The consumption of sweetened beverages decreased during the period. However, a significant portion of the population still referred a daily consumption of these beverages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 43 publications
3
16
0
4
Order By: Relevance
“…Regarding the increase in the recommended consumption of fruits and vegetables and reduction in the consumption of fat-rich meat or soft drinks, similar results can be found in other studies [24,28,29]. Although the objective of the present study is not to investigate the causes of the observed trends, the implementation of programs and public policies in line with national plans to fight NCD and to prevent and control obesity may contribute to the trend towards improvement in the food consumption of the population of Belo Horizonte [5,8].…”
Section: Discussionsupporting
confidence: 88%
“…Regarding the increase in the recommended consumption of fruits and vegetables and reduction in the consumption of fat-rich meat or soft drinks, similar results can be found in other studies [24,28,29]. Although the objective of the present study is not to investigate the causes of the observed trends, the implementation of programs and public policies in line with national plans to fight NCD and to prevent and control obesity may contribute to the trend towards improvement in the food consumption of the population of Belo Horizonte [5,8].…”
Section: Discussionsupporting
confidence: 88%
“…The time lag of the data collection is another limitation, since the data was collected in 2008. However, it does not diminish the findings of this study considering that few researches in national literature investigated the same research question in a population-based study 10 . In addition, this investigation used data from a representative sample of one of the world's largest cities that is an important financial center of South America, and a migrant destination for different parts of Brazil and other countries.…”
Section: Discussionmentioning
confidence: 58%
“…However, a downward trend in the intake of soft drinks and artificial juices in adults living in Brazilian capitals and Federal District from 2009 to 2016 was reported by the Surveillance System of Risk and Protection Factors for Chronic Diseases by Telephone Survey (VIGITEL). The reduction was especially seen in those aged between 18 and 44 years, with more than 12 years of study, with a partner, and residents of more developed regions 10 . Despite these significant findings, it is important to be aware of the limitations of the questionnaire used to collect dietary data in this survey, as well as the fact that the beverages investigated does not include all SSB, as addressed by the authors 10 .…”
Section: Rev Bras Epidemiol 2020; 23: E200003mentioning
confidence: 95%
See 1 more Smart Citation
“…O consumo de refrigerante e outras bebidas com açúcar livre é preocupante, não apenas pelo fato de seu valor nutricional ser extremamente baixo, sua capacidade de promover saciedade ser reduzida, como também por estar relacionado com o aumento de peso e com outras doenças, como a síndrome metabólica, resistência insulínica, diabetes mellitus tipo II e obesidade abdominal (20) .…”
Section: Métodounclassified